2019
DOI: 10.1038/s41372-019-0508-5
|View full text |Cite
|
Sign up to set email alerts
|

Utility of echocardiography in predicting mortality in infants with severe bronchopulmonary dysplasia

Abstract: Objective To determine the relationship between interventricular septal position (SP) and right ventricular systolic pressure (RVSP) and mortality in infants with severe BPD (sBPD). Study design Infants with sBPD in the Children's Hospitals Neonatal Database who had echocardiograms 34-44 weeks' postmenstrual age (PMA) were included. SP and RVSP were categorized normal, abnormal (flattened/bowed SP or RVSP > 40 mmHg) or missing. Results Of 1157 infants, 115 infants (10%) died. Abnormal SP or RVSP increased mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These included increasing FiO2 need and PaCO2 levels, pulmonary hypertension with only partial response to pulmonary vasodilator therapies, and recurrent cyanotic or hypoxemic episodes requiring frequent sedation with multiple pharmacologic agents. Our data supports previous reports of increased mortality in patients with documented pulmonary hypertension in BPD 22–24 . A large multicenter study has shown a relationship between tracheobronchomalacia, airway collapse, mechanical ventilation, and morbidity in severe or grade 3 BPD 25 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These included increasing FiO2 need and PaCO2 levels, pulmonary hypertension with only partial response to pulmonary vasodilator therapies, and recurrent cyanotic or hypoxemic episodes requiring frequent sedation with multiple pharmacologic agents. Our data supports previous reports of increased mortality in patients with documented pulmonary hypertension in BPD 22–24 . A large multicenter study has shown a relationship between tracheobronchomalacia, airway collapse, mechanical ventilation, and morbidity in severe or grade 3 BPD 25 .…”
Section: Discussionsupporting
confidence: 91%
“…Our data supports previous reports of increased mortality in patients with documented pulmonary hypertension in BPD. [22][23][24] A large multicenter study has shown a relationship between tracheobronchomalacia, airway collapse, mechanical ventilation, and morbidity in severe or grade 3 BPD. 25 In our cases, bedside flexible bronchoscopy performed during hypoxemic episodes did not confirm severe airway collapse as the primary trigger, although airway malacia was usually present.…”
Section: Resultsmentioning
confidence: 99%
“…Standards for timing and interpretation of screening echocardiogram for BPD-PH or elevated pulmonary pressures associated with evolving BPD remain unclear ( 36 , 37 ). However, echocardiogram screening for PH before 36 weeks may influence early approaches to mitigate PH, such as ventilator strategies, PDA/ASD closure, and avoidance of aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…PH contributes significantly to the severity of BPD and, when severe, is associated with a high rate of mortality ( 19 , 20 ). Unfortunately, the pathophysiology of PH is as complex as that of BPD.…”
Section: Bpd-related Pulmonary Hypertensionmentioning
confidence: 99%